The Signatures on Juan O'Gorman's Early Functionalist Houses - López Uribe, Cristina (Facultad de Arquitectura, Universidad Nacional Autónoma de México, 2016)
This essay is centered on new discoveries that put into crisis the history of Juan O’Gorman’s O’Gorman House and the House and Studio of Diego Rivera: a signature on the façade of the former and, as a result of detailed analysis of recently discovered photographs, the proof of the existence of a signature on the latter. Through these signatures, the traditional history of functionalist architecture in Mexico, its beginnings and its relationship to contemporary ideas of art can be reevaluated and corrected. A contexualized re-reading of the writings of the architect, with this new information, yields a more nuanced and complex idea regarding the various debates of art and architecture that are central to understanding his production in the 1930s.